On the differential advantages of evergreenness and deciduousness in mediterranean oak woodlands: a flux perspective - Baldocchi, Dennis D.; Ma, Siyan; Rambal, Serge; Misson, Laurent; OURCIVAL, JEAN-MARC; Limousin, Jean-Marc; Pereira, João; Papale, Dario (ECOLOGICAL APPLICATIONS, 2010)
We assessed the differential advantages of deciduousness and evergreenness by examining 26 site-years of carbon dioxide, water vapor, and energy flux measurements from five comparable oak woodlands in France, Italy, Portugal, and California (USA). On average, the evergreen and deciduous oak woodlands assimilated and respired similar amounts of carbon while using similar amounts of water. These results suggest that evergreen and deciduous woodlands have specific, and similar, ecological costs in mediterranean climates, and that both leaf habits are able to meet these costs. What are the mechanisms behind these findings? Deciduous oaks compensated for having a shorter growing season by attaining a greater capacity to assimilate carbon for a given amount of intercepted solar radiation during the well-watered spring period; at saturating light levels, deciduous oaks gained carbon at six times the rate of evergreen oaks. Otherwise, the two leaf habits experienced similar efficiencies in carbon use (the change in carbon respired per change in carbon assimilated), water use (the change in carbon assimilation per change in water evaporated), and rainfall use (the change in evaporation per change in rainfall). Overall, leaf area index, rather than leaf habit, was the significant factor in determining the absolute magnitude of carbon gained and water lost by each evergreen and deciduous oak woodland over an annual interval; the closed canopies assimilated and respired more carbon and transpired more water than the open canopies. Both deciduous and evergreen mediterranean oaks survive in their seasonally hot/dry, wet/cool native range by ensuring that actual evaporation is less than the supply of water. This feat is accomplished by adjusting the leaf area index to reduce total water loss at the landscape scale, by down-regulating photosynthesis, respiration, and stomatal conductance with progressive seasonal soil water deficits, and by extending their root systems to tap groundwater.
The following values have no corresponding Zotero field: pub-location: 1990 M STREET NW, STE 700, WASHINGTON, DC 20036 USA publisher: ECOLOGICAL SOC AMER
Keywords: carbon dioxide exchange; deciduousness vs. evergreen

Remote estimation of carbon dioxide uptake by a Mediterranean forest - Garbulsky, Martín F.; Penuelas, Josep; Papale, Dario; Filella, Iolanda (Global Change Biology, 2008)
The estimation of the carbon balance in ecosystems, regions, and the biosphere is currently one of the main concerns in the study of the ecology of global change. Current remote sensing methodologies for estimating gross primary productivity are not satisfactory because they rely too heavily on (i) the availability of climatic data, (ii) the definition of land-use cover, and (iii) the assumptions of the effects of these two factors on the radiation-use efficiency of vegetation (RUE). A new methodology is urgently needed that will actually assess RUE and overcome the problems associated with the capture of fluctuations in carbon absorption in space and over time. Remote sensing techniques such as the widely used reflectance vegetation indices (e.g. NDVI, EVI) allow green plant biomass and therefore plant photosynthetic capacity to be assessed. However, there are vegetation types, such as the Mediterranean forests, with a very low seasonality of these vegetation indices and a high seasonality of carbon uptake. In these cases it is important to detect how much of this capacity is actually realized, which is a much more challenging goal. The photochemical reflectance index (PRI) derived from freely available satellite information (MODIS sensor) presented for a 5-year analysis for a Mediterranean forest a positive relationship with the RUE. Thus, we show that it is possible to estimate RUE and GPP in real time and therefore actual carbon uptake of Mediterranean forests at ecosystem level using the PRI. This conceptual and technological advancement would avoid the need to rely on the sometimes unreliable maximum RUE.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: carbon cycle; CO2 uptake; eddy covariance; Mediterranean forests; MODIS; primary productivity; radiation use efficiency; Remote sensing; Vegetation

Remote estimation of carbon dioxide uptake by a Mediterranean forest - GARBULSKY, MARTÍN F; Penuelas, Josep; Papale, Dario; Filella, Iolanda (Global Change Biology, 2008)
The estimation of the carbon balance in ecosystems, regions, and the biosphere is currently one of the main concerns in the study of the ecology of global change. Current remote sensing methodologies for estimating gross primary productivity are not satisfactory because they rely too heavily on (i) the availability of climatic data, (ii) the definition of land-use cover, and (iii) the assumptions of the effects of these two factors on the radiation-use efficiency of vegetation (RUE). A new methodology is urgently needed that will actually assess RUE and overcome the problems associated with the capture of fluctuations in carbon absorption in space and over time. Remote sensing techniques such as the widely used reflectance vegetation indices (e.g. NDVI, EVI) allow green plant biomass and therefore plant photosynthetic capacity to be assessed. However, there are vegetation types, such as the Mediterranean forests, with a very low seasonality of these vegetation indices and a high seasonality of carbon uptake. In these cases it is important to detect how much of this capacity is actually realized, which is a much more challenging goal. The photochemical reflectance index (PRI) derived from freely available satellite information (MODIS sensor) presented for a 5-year analysis for a Mediterranean forest a positive relationship with the RUE. Thus, we show that it is possible to estimate RUE and GPP in real time and therefore actual carbon uptake of Mediterranean forests at ecosystem level using the PRI. This conceptual and technological advancement would avoid the need to rely on the sometimes unreliable maximum RUE.
Keywords: carbon cycle; CO2 uptake; eddy covariance; Mediterranean forests; MODIS; primary productivity; radiation use efficiency; Remote sensing; Vegetation